Effects of riparian forests restoration on the structure and functioning of tropical streams - Ogasawara, Matheus Eijii Kinchoku (2025)
Tropical freshwater ecosystems harbor rich aquatic biodiversity and provide essential ecosystem services. However, they are among the most threatened ecosystems worldwide. In Brazil, stream restoration is still in its early stages, and the effects of forest restoration on tropical stream ecosystems remain largely unexplored. The limited empirical data on how tropical streams respond to riparian and in-stream restoration efforts make it challenging to predict their potential benefits. Given this context, this thesis aims to advance the understanding of how restored riparian forests contribute to the structural and functional recovery of tropical stream ecosystems. Specifically, it evaluates the capacity of riparian forests under different restoration timeframes to supply large wood and provide shadingtwo key mechanisms through which riparian vegetation influences stream hydrology, habitat complexity, and primary productivity. As a secondary objective, the study investigates how variations in these inputs affect critical stream ecosystem functions, including nutrient dynamics, organic matter processing, and algal biomass accumulation. The second chapter of this thesis evaluates how the structural development of restored riparian forests influences the physical, chemical, and biological conditions of streams. The third chapter investigates the impact of large wood addition on the structural attributes and functions of two headwater streams in southeastern Brazil. The fourth chapter evaluates the combined effects of shade and channel complexity on primary productivity in southeastern Brazilian streams through a mesocosm experiment. The findings indicate that as riparian forests mature, it provides more canopy cover and large wood, with significant improvements occurring only after 40 years of restoration. The manipulation of stream channel complexity has a substantial effect on channel morphology, increasing physical habitat availability, depth, and wetted width, which in turn influences water velocity and residence time. Regarding to the mesocosms experiment, light availability is a key driver of primary productivity, particularly for chlorophyll a, while the interactions highlight that primary productivity in lotic environments is not solely driven by light intensity but rather shaped by a combination of physical and environmental factors. This thesis provides critical insights into the realistic expectations for riparian forest restoration impacts on streams. In light of this, it is important to consider the catchment conditions alongside riparian forest recovery. Additionally, in-stream interventions such as large wood additions may be necessary to enhance channel complexity during the restoration process, helping to accelerate the recovery of key ecological functions that regulate water quality and flow. The findings of this study can be used to guide future riparian forest restoration projects and assist in the selection of strategies that will ensure improvements in the conditions of degraded streams in Brazil and the neotropics in general.